2012 34th International Conference on Software Engineering (ICSE) 2012
DOI: 10.1109/icse.2012.6227170
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study about the effectiveness of debugging when random test cases are used

Abstract: Abstract-Automatically generated test cases are usually evaluated in terms of their fault revealing or coverage capability. Beside these two aspects, test cases are also the major source of information for fault localization and fixing. The impact of automatically generated test cases on the debugging activity, compared to the use of manually written test cases, has never been studied before.In this paper we report the results obtained from two controlled experiments with human subjects performing debugging ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Research has also identified other reasons why developers are not comfortable with blindly trusting auto-generated code. For example, generated code might be less readable and maintainable [7] [13].…”
Section: Introductionmentioning
confidence: 99%
“…Research has also identified other reasons why developers are not comfortable with blindly trusting auto-generated code. For example, generated code might be less readable and maintainable [7] [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study by Ceccato et al revealed that random test cases are not harder to debug than manual test cases, on the contrary, due to their intrinsic simplicity, are often easier to debug [28].…”
Section: Guided Random Testingmentioning
confidence: 97%
“…Pure RT [14][15][16][17][18][19] Adaptive RT [20][21][22][23][24] Recent advances in random testing (2010)(2011)(2012)(2013)(2014) Guided RT [25][26][27][28] Fuzz testing [29][30][31] …”
Section: Random Testingmentioning
confidence: 99%
“…This has been largely solved by Delta Debugging [45], an automated greedy search for small failure-inducing test cases. In fact, there is some evidence that debugging based on short random test cases is easier than debugging based on human-created test cases [3]. A second problem is the sheer volume of output: an overnight run of a fuzzer may result in hundreds or thousands of failure-inducing test cases.…”
Section: Introductionmentioning
confidence: 99%